Hydrodechlorination catalyst with modified zsm-5 composite carrier based on saccharide template and preparation method thereof

By modifying the ZSM-5 composite support to support the Ni2P catalyst, acid-base synergistic properties were constructed, which improved the low-temperature activity and anti-poisoning ability of the catalyst, achieving efficient and deep removal of organochlorines. This solved the problems of insufficient catalyst activity and easy poisoning in the existing technology, and is suitable for the gasification and purification of organic solid waste.

CN122625262APending Publication Date: 2026-08-25QINGDAO UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610920421.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing Ni2P-based hydrodechlorination catalysts have insufficient low-temperature removal activity and weak resistance to poisoning in organic solid waste gasification fuels, making it difficult to meet practical engineering needs.

Method used

A hydrogenation dechlorination catalyst for Ni2P crystal faces was supported on a ZSM-5 composite support modified with a sugar template. Through polysaccharide hydrogen bond anchoring and functional group chelation modification technology, an LDH-hierarchical porous ZSM-5 composite support was constructed. Combined with citric acid and ethylene glycol regulation strategies, the highly active bi-crystal faces of Ni2P (201) and (211) were preferentially induced to grow, thus constructing an acid-base bifunctional structure and realizing the integration of organochlorine catalytic conversion and by-product immobilization.

Benefits of technology

It significantly improves the low-temperature hydrodechlorination activity and anti-poisoning ability of the catalyst, realizes the efficient and deep removal of organic chlorine, solves the problems of poor low-temperature activity and easy chlorine poisoning of traditional catalysts, and meets the low-temperature purification requirements of organic solid waste gasification fuel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122625262A_ABST
    Figure CN122625262A_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on saccharide template modified ZSM-5 composite carrier load crystal face Ni2P hydrogen dechlorination catalyst and preparation method, belong to the preparation technical field of dechlorination catalyst.The method includes: first with polysaccharide modified porous ZSM-5 as main body, with LDH base carrier and be compounded to prepare LDH-multistage hole ZSM-5 composite carrier;Afterwards, nickel nitrate, citric acid and ethylene glycol are mixed, and impregnation solution is prepared, and the composite carrier of preparation load nickel base precursor;Finally, the composite carrier of load nickel base precursor is with sodium hypophosphite in nitrogen atmosphere, in situ induction Ni2P (201) Crystal face, Ni2P (211) Crystal face preferential growth, after cooling, passivation treatment, obtain immediately.The hydrogen dechlorination catalyst prepared by the application has excellent low-temperature activity, strong resistance to poisoning and high operating stability, and can achieve efficient and economic deep removal of organic chlorine in the low-temperature purification process of organic solid waste gasification fuel gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dechlorination catalyst preparation technology, specifically relating to a hydrogenation dechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes and its preparation method. Background Technology

[0002] With the continuous increase in the production of organic solid waste, its resource utilization has become a key link in promoting green, low-carbon, and circular development. Staged pyrolysis gasification technology for organic solid waste can convert carbon-containing organic solid waste into syngas for resource recovery. With its wide material adaptability and high energy recovery efficiency, it has become a core technological path for the resource-based and clean utilization of organic solid waste. However, chlorine in organic solid waste is easily converted into organochlorine pollutants during pyrolysis gasification. Organochlorine not only severely corrodes gasification and subsequent gas treatment equipment, but it is also a key precursor for the formation of highly toxic dioxins, easily causing serious secondary environmental pollution problems. Therefore, the efficient and stable removal of organochlorine from gasification fuel gas is a pressing technical challenge that needs to be addressed in the field of organic solid waste gasification and purification.

[0003] Currently, organochlorine removal technologies mainly include adsorption, absorption, and catalytic hydrodechlorination. Among them, catalytic hydrodechlorination can directionally convert organochlorine into harmless hydrocarbons and hydrogen chloride, and has the advantages of high removal efficiency, no secondary pollution, and suitability for continuous gas-phase treatment, making it the mainstream technology for deep purification of organochlorine. The catalyst is the core factor that determines the hydrodechlorination effect. Ni2P metal phosphides have a broad application prospect in the field of organochlorine catalytic removal due to their excellent low-temperature hydrogenation activity and anti-carbon deposition ability. However, existing Ni2P-based hydrodechlorination catalysts still have many shortcomings under the complex working conditions of actual gasification of fuel gas, mainly: (1) Conventional Ni2P catalysts have disordered crystal surface growth, limited low-temperature hydrogenation activity, and poor stability. Traditional control and preparation processes are prone to pollution and poisoning of active sites. (2) A single support structure is difficult to balance the efficient activation of organochlorine and the in-situ fixation of hydrogen chloride. The catalyst has weak resistance to chlorine poisoning and short service life. The overall purification effect is difficult to meet the actual engineering requirements.

[0004] Therefore, it is evident that the insufficient low-temperature removal activity and weak resistance to poisoning of existing Ni2P-based hydrodechlorination catalysts are key factors affecting the deep removal of organochlorines, indicating that the existing technology needs further improvement. Summary of the Invention

[0005] One of the objectives of this invention is to provide a method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support with Ni2P crystal planes. This method solves the technical problems of insufficient low-temperature removal activity of organochlorines in organic solid waste gasification fuel and easy chlorine poisoning of the catalyst. The hydrodechlorination catalyst prepared by this invention has excellent low-temperature activity, strong resistance to poisoning, and high operational stability, and can achieve efficient and economical deep removal of organochlorines in the low-temperature purification process of organic solid waste gasification fuel.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a hydrodechlorination catalyst based on a sugar-templated modified ZSM-5 composite support supporting Ni2P crystal planes, the preparation method comprising the following steps: a. Preparation of LDH-hierarchical porous ZSM-5 composite carrier: Polysaccharide-modified porous ZSM-5 is used as the main body and compounded with LDH-based carrier. After dispersion, drying and calcination, LDH-hierarchical porous ZSM-5 composite carrier is obtained; wherein, the mass ratio of polysaccharide-modified porous ZSM-5 to LDH-based carrier is 1~4:1~4. b. Preparation of composite support for nickel-based precursor: Nickel nitrate, citric acid and ethylene glycol are mixed to prepare an impregnation solution; the LDH-hierarchical porous ZSM-5 composite support is placed in the impregnation solution, and a water bath constant temperature equal volume impregnation method is used. Through the interfacial confinement of the LDH-hierarchical porous ZSM-5 composite support and the coordination effect of ethylene glycol, the nickel active component is uniformly anchored and its growth sites are controlled. After impregnation, the composite support for nickel-based precursor is obtained by constant temperature drying. c. The composite carrier supporting the nickel-based precursor and sodium hypophosphite are placed in a tubular reactor, and the Ni2P201 and Ni2P211 crystal planes are preferentially grown in situ under a nitrogen atmosphere. After the reaction is completed, the mixture is cooled and passivated under an inert atmosphere, and then granulated, crushed, and sieved to obtain 40-60 mesh particles.

[0007] The preparation method of the above-mentioned hydrodechlorination catalyst based on Ni2P supported on a ZSM-5 composite support modified with a sugar template, in step a, the preparation steps of polysaccharide-modified porous ZSM-5 are as follows: using green biological polysaccharide as a template, it is thoroughly mixed with porous ZSM-5 precursor, and the hydroxyl groups on the surface of biological polysaccharide are used to form hydrogen bonds with the 010 crystal facet of ZSM-5 precursor to anchor and control the crystal facet morphology; the resulting mixed gel is placed in a hydrothermal reactor for hydrothermal crystallization reaction, after crystallization, it is cooled to room temperature, dried, and then the precursor powder is placed in a muffle furnace for calcination, and after grinding and filtration, the catalyst is obtained.

[0008] The above-mentioned method for preparing a hydrogenation dechlorination catalyst based on a sugar-template modified ZSM-5 composite support with Ni2P crystal planes includes a green biopolysaccharide, which is sodium alginate or chitosan. A porous ZSM-5 precursor is prepared by hydrothermal crystallization at a temperature of 160–200°C for 12 hours. The precursor is then calcined in a muffle furnace at 400–500°C for 2–3 hours, during which the green biopolysaccharide is thermally desorbed.

[0009] The above-mentioned method for preparing a hydrogenation dechlorination catalyst based on a sugar template modified ZSM-5 composite support for supporting Ni2P crystal planes includes the following steps in step a: calcining layered double hydroxide LDH to obtain layered bimetallic oxide LDO; dispersing the obtained layered bimetallic oxide LDO powder in an aqueous solution of NH4H2PO4; utilizing the LDO memory effect to complete structural reconstruction and anion intercalation; subsequently adding nickel formate and a transition metal salt solution and mixing them evenly to construct interface sites suitable for the subsequent growth of Ni2P active components; and then drying and calcining to obtain the LDH-based support.

[0010] In the above-mentioned method for preparing a hydrogenation dechlorination catalyst based on a sugar template modified ZSM-5 composite support supporting Ni2P crystal plane, in step a, the calcination temperature is 500℃ and the calcination time is 4h, and the roasting temperature is 400~500℃ and the roasting time is 2~3h.

[0011] In the above-mentioned method for preparing a hydrogenation dechlorination catalyst based on a sugar template modified ZSM-5 composite support supporting Ni2P crystal plane, in step a, the transition metal salt is an iron salt, a cobalt salt, or a copper salt, the mass fraction of the NH4H2PO4 aqueous solution is 5% to 15%, and the anion intercalation stirring time is 5 to 6 hours.

[0012] In the above-mentioned method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystals, step b includes the following steps: the impregnation temperature is 60℃, the impregnation time is 6h; the molar ratio of citric acid to ethylene glycol is 1:1 to 3; the loading of metallic nickel in the hydrodechlorination catalyst is 5 to 15 wt%; and the isothermal drying temperature is 100 to 120℃, and the drying time is 6 to 12h.

[0013] Further preferred, the molar ratio of citric acid to ethylene glycol is 1:2.

[0014] In the preparation method of the above-mentioned hydrogenation dechlorination catalyst based on the ZSM-5 composite support modified with a sugar template and supported on Ni2P crystal face, in step c, the composite support supporting the nickel-based precursor and sodium hypophosphite are placed in a tubular reactor and the Ni:P molar ratio is controlled to be 1-2:1-2; the reaction temperature in the tubular reactor is 250-350℃ and the isothermal reaction time is 1-3h.

[0015] In the above-mentioned method for preparing a hydrogenation dechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes, in step c, the reaction is carried out under a nitrogen inert atmosphere, and the nitrogen gas flow rate is controlled at 50 mL / min.

[0016] A hydrodechlorination catalyst based on Ni2P supported on a sugar-template modified ZSM-5 composite support was prepared using the method described above. The dechlorination conditions of the hydrodechlorination catalyst were: 20 ml / min. ‐1 A mixture of chlorobenzene and nitrogen gas at 20 ml / min ‐1 The H2 in the mixture is 100 ppm chlorobenzene, the dechlorination temperature is 300℃, and the dechlorination time is 30 min.

[0017] The principle of the preparation method of the hydrodechlorination catalyst based on Ni2P supported on a ZSM-5 composite support modified with a sugar template in this invention is as follows: This invention prepares functionalized hierarchical porous ZSM-5 through polysaccharide hydrogen bond anchoring and functional group chelation modification technology, and combines it with LDH support that has been calcined, reconstructed, and anion-intercalated to construct a composite support system of LDH-hierarchical porous ZSM-5 with a synergistic effect of layered confinement and crystal facet anchoring. Combined with citric acid and ethylene glycol regulation strategies, the highly active Ni2P (201) and (211) bicrystalline faces are selectively exposed in a directional manner. Relying on the synergistic effect of the bicrystalline faces and the hierarchical porous structure of the support, the hydrogen overflow effect is enhanced, effectively improving the low-temperature C-Cl bond activation and breaking ability. At the same time, the composite support has dual acid-base functions. The acidic sites of ZSM-5 activate organochlorines, and the basic sites of LDH can adsorb and fix the HCl generated by the reaction in situ, realizing the integration of organochlorine catalytic conversion and by-product immobilization, and inhibiting the formation of dioxin precursors from the source. This invention uses natural polysaccharide green templates to replace traditional organic amine templates, combined with a mild and green crystal facet control process. The preparation process is green and environmentally friendly with controllable costs. The prepared hydrodechlorination catalyst effectively solves the defects of traditional dechlorination catalysts, such as poor low-temperature activity, easy chlorine poisoning, and weak stability.

[0018] Compared with the prior art, the present invention brings the following beneficial technical effects:

[0019] (1) Constructing a functionally synergistic composite support system. In the preparation of LDH-based support, the layered double hydroxide LDH is calcined and reconstructed and modified by anion intercalation. At the same time, ZSM-5 molecular sieve is modified by green biological polysaccharide. Through the dual effect of LDH layer confinement and ZSM-5 (010) crystal plane hydrogen bond anchoring, the preferential growth of Ni2P (201) and (211) double crystal planes is induced, realizing a high proportion of exposure of highly active crystal planes, which greatly improves the low-temperature hydrogenation dechlorination activity of the catalyst and solves the problem of disordered crystal planes and poor low-temperature performance of traditional Ni2P catalysts.

[0020] (2) Green composite additives are used to regulate the process. The present invention uses a compound regulation system of citric acid and ethylene glycol. The process formulation is mild and the preparation process is green and pollution-free. It can reduce the damage to active sites that are easily caused by conventional processes. The process stability and adaptability are stronger, and it effectively improves the shortcomings of traditional crystal facet regulation processes, such as poor adaptability to operating conditions and rapid catalyst performance decay.

[0021] (3) Achieving multifunctional modification and green preparation of polysaccharides. This invention uses natural polysaccharides as green templates to replace traditional highly toxic and costly organic amine template agents. It can not only construct multi-level channels to optimize mass transfer efficiency and modify surface defects of molecular sieves, but also chelate and fix nickel and phosphorus metal precursors through hydroxyl and carboxyl functional groups, effectively improving the dispersion uniformity of active components and avoiding the aggregation and deactivation of active particles.

[0022] (4) Achieving synergistic effect of integrated catalysis and chlorine fixation. The LDH-hierarchical porous ZSM-5 composite support constructed in this invention has excellent acid-base synergistic properties. It relies on the acidic sites of ZSM-5 to efficiently activate the C-Cl bonds of organic chlorine, and combines the alkaline sites of LDH to adsorb and fix hydrogen chloride byproducts in situ, which significantly alleviates the problem of chlorine poisoning of the catalyst. At the same time, it inhibits the formation of dioxin precursors from the source, greatly improves the catalyst's cycle stability and adaptability to complex working conditions, and meets the engineering requirements of low-temperature deep purification of organic solid waste gasification fuel. Attached Figure Description

[0023] The present invention will be further described below with reference to the accompanying drawings: Figure 1 This is a comparison chart of the dechlorination efficiency and HCl selectivity of the hydrodechlorination catalysts prepared in Examples 1-7 and Comparative Examples 1-3 of this invention; Figure 2 The image shows a SEM image of the hydrodechlorination catalyst prepared in Example 1 of this invention. Figure 3 , Figure 4 This is a TEM image of the hydrodechlorination catalyst prepared in Example 1 of the present invention. Detailed Implementation

[0024] This invention proposes a method for preparing a hydrogenation dechlorination catalyst based on a sugar-template modified ZSM-5 composite support with Ni2P crystal planes. To make the advantages and technical solutions of this invention clearer and more explicit, the invention will be further described below with reference to specific embodiments.

[0025] All the raw materials mentioned in this invention can be purchased through commercial channels.

[0026] The specific testing method for the hydrodechlorination catalyst prepared by this invention is as follows: the prepared hydrodechlorination catalyst is placed in an organic solid waste pyrolysis simulation device in the prior art, and 20 ml·min is introduced into it. ‐1 H2 and 20 ml·min ‐1 A mixture of chlorobenzene and nitrogen (with a chlorobenzene concentration of 100 ppm) was heated to 300°C and held at that temperature for 30 minutes. The incoming and outgoing gases were then analyzed by gas chromatography.

[0027] Example 1: A method for preparing a hydrodechlorination catalyst based on a sugar-templated modified ZSM-5 composite support supporting Ni2P crystals includes the following steps: Step 1: Preparation of LDH-hierarchical porous ZSM-5 composite support: Pure LDH material was placed in a muffle furnace and heated to 500℃ at a rate of 10℃ / min, and calcined at this temperature for 4 hours to obtain LDO layered bimetallic oxide. LDO powder was dispersed in a 10% (w / w) aqueous solution of NH4H2PO4 and stirred at room temperature for 5 hours to utilize the LDO memory effect to complete structural reconstruction and phosphate anion intercalation. Subsequently, a mixed metal salt solution of nickel formate and ferric nitrate nonahydrate was slowly added and thoroughly mixed to construct interface sites suitable for Ni2P growth. The mixed slurry was dried at 120℃ for 12 hours and calcined at 450℃ for 3 hours to obtain the LDH-based support.

[0028] Using sodium alginate as a green polysaccharide template, hierarchical ZSM-5 molecular sieves were prepared by hydrothermal crystallization at a crystallization temperature of 180℃ and a crystallization time of 12h. Hydrogen bonds were formed between the hydroxyl groups on the surface of sodium alginate and the (010) crystal facets of ZSM-5 to regulate the crystal morphology and chelate the active precursor. After drying, the crystallized product was calcined at 450℃ for 2h to completely remove the polysaccharide template and construct a hierarchical porous structure in situ, thus obtaining functionalized hierarchical ZSM-5 molecular sieves.

[0029] The obtained polysaccharide-modified porous ZSM-5 was compounded with LDH-based support at a mass ratio of 1:1, and deionized water was added and stirred thoroughly to disperse the mixture. After conventional drying and calcination at 450℃, the LDH-multi-level porous ZSM-5 composite support was obtained.

[0030] Step 2: Preparation of composite supports for nickel-based precursors: Nickel nitrate was weighed according to the theoretical nickel loading of 10wt%, and a homogeneous impregnation solution was prepared by mixing it with citric acid and ethylene glycol in a molar ratio of 1:2. The composite carrier was placed in the impregnation solution and impregnated at a constant temperature of 60℃ for 6 hours. The nickel precursor was uniformly anchored through the interface confinement of the carrier and the coordination of the additives. After impregnation, the composite carrier loaded with nickel-based precursor was dried at a constant temperature of 110℃ for 8 hours to obtain the composite carrier.

[0031] Step 3: Weigh sodium hypophosphite according to a Ni / P molar ratio of 1:1, mix it uniformly with the composite support carrying the nickel precursor, place it in a tubular reactor, and purify it with high-purity nitrogen gas throughout the process. The gas flow rate is 50 mL / min, and the phosphating reaction is carried out at a constant temperature of 300℃ for 2 hours to induce the preferential growth of Ni2P (201) and (211) highly active crystal faces in situ. After the reaction, cool it under a nitrogen atmosphere and passivate it with a low-concentration oxygen-nitrogen mixture. After granulation, crushing, and sieving, select 40-60 mesh particles to obtain the hydrodechlorination catalyst. Figure 2 The image shows a SEM image of the hydrodechlorination catalyst prepared in Example 1 of this invention. Figure 3 , Figure 4 The images shown are TEM images of the hydrodechlorination catalyst prepared in Example 1 of this invention, representing the Ni2P (201) and Ni2P (211) crystal planes, respectively.

[0032] Results: The hydrodechlorination catalyst prepared in this embodiment was applied to remove organic chlorine from organic solid waste gas. The specific removal reaction was as follows: H2 reacted on the catalyst to generate active H, and the C-Cl bond in the organic chlorine was broken on the catalyst to generate benzene and HCl.

[0033] As can be seen from the above, the hydrodechlorination catalyst prepared in this embodiment can effectively remove chlorine from organochlorine and generate HCl, with an organochlorine removal efficiency of up to 95% and an HCl selectivity of up to 96%.

[0034] Example 2: The difference from Example 1 is that in step one, the mass ratio of LDH-based support to polysaccharide-modified porous ZSM-5 is 4:1.

[0035] Results: The hydrodechlorination catalyst prepared in this embodiment can effectively remove chlorine from organochlorine compounds and generate HCl. The removal efficiency of organochlorine compounds can reach 87%, and the selectivity of HCl can reach 90%.

[0036] Example 3: The difference from Example 1 is that in step one, the mass ratio of LDH-based support to polysaccharide-modified porous ZSM-5 is 2:1.

[0037] Results: The hydrodechlorination catalyst prepared in this embodiment can effectively remove chlorine from organochlorine compounds and generate HCl. The removal efficiency of organochlorine compounds can reach 89%, and the selectivity of HCl can reach 91%.

[0038] Example 4: The difference from Example 1 is that in step one, the mass ratio of LDH-based support to polysaccharide-modified porous ZSM-5 is 1:2.

[0039] Results: The hydrodechlorination catalyst prepared in this embodiment can effectively remove chlorine from organochlorine and generate HCl. The removal efficiency of organochlorine can reach 90%, and the selectivity of HCl can reach 92%.

[0040] Example 5: The difference from Example 1 is that in step one, the mass ratio of LDH-based support to polysaccharide-modified porous ZSM-5 is 1:4.

[0041] Results: The hydrodechlorination catalyst prepared in this embodiment can effectively remove chlorine from organochlorine compounds and generate HCl. The removal efficiency of organochlorine compounds can reach 85%, and the selectivity of HCl can reach 88%.

[0042] Example 6: The difference from Example 1 is that in step two, the molar ratio of citric acid to ethylene glycol is 1:1.

[0043] Results: The hydrodechlorination catalyst prepared in this embodiment can effectively remove chlorine from organochlorine and generate HCl. The removal efficiency of organochlorine can reach 86%, and the selectivity of HCl can reach 85%.

[0044] Example 7: The difference from Example 1 is that in step two, the molar ratio of citric acid to ethylene glycol is 1:3.

[0045] Results: The hydrodechlorination catalyst prepared in this embodiment can effectively remove chlorine from organochlorine and generate HCl. The removal efficiency of organochlorine can reach 83%, and the selectivity of HCl can reach 84%.

[0046] Comparative Example 1: A method for preparing a hydrodechlorination catalyst includes the following steps: Step 1: Use porous ZSM-5 molecular sieve as a support; Step 2: Preparation of the support for the nickel-based precursor: Nickel nitrate was weighed according to the theoretical nickel loading of 10wt%, and a homogeneous impregnation solution was prepared by mixing it with citric acid and ethylene glycol in a molar ratio of 1:2. The porous ZSM-5 molecular sieve support was placed in the impregnation solution and impregnated at a constant temperature of 60℃ in a water bath for 6 hours. The nickel precursor was uniformly anchored through the interface confinement of the support and the coordination of the additives. After impregnation, the support was dried at a constant temperature of 110℃ for 8 hours to obtain the support loaded with the nickel-based precursor.

[0047] Step 3: Weigh sodium hypophosphite according to a Ni / P molar ratio of 1:1, mix it uniformly with the carrier supporting the nickel precursor, place it in a tubular reactor, and purify it with high-purity nitrogen gas throughout the process. The gas flow rate is 50 mL / min, and the phosphating reaction is carried out at a constant temperature of 300℃ for 2 hours to induce the preferential growth of Ni2P (201) and (211) highly active crystal faces in situ. After the reaction, cool it under a nitrogen atmosphere and passivate it with a low-concentration oxygen-nitrogen mixture. After granulation, crushing, and sieving, select 40-60 mesh particles to obtain the hydrodechlorination catalyst.

[0048] Results: The hydrodechlorination catalyst prepared in this comparative example can remove organochlorine and generate HCl, with an organochlorine removal efficiency of 78% and an HCl selectivity of 82%.

[0049] Comparative Example 2: A method for preparing a hydrodechlorination catalyst includes the following steps: Step 1: Using tetrapropylammonium hydroxide (TPAOH) aqueous solution as the organic structure guiding template, TPAOH, silicon source, aluminum source, and deionized water were mixed and stirred continuously to prepare a homogeneous silica-alumina gel. The mixed gel was transferred to a hydrothermal reactor and hydrothermally crystallized at 180℃ for 12 hours. After cooling, the crystallized product was filtered, washed with water until neutral, dried thoroughly at 120℃, and then calcined in a muffle furnace at 450℃ for 2 hours to completely remove the organic amine template, yielding a conventional single-channel ZSM-5 molecular sieve.

[0050] Step 2: Preparation of the support for the nickel-based precursor: Nickel nitrate was weighed according to the theoretical nickel loading of 10wt%, and a homogeneous impregnation solution was prepared by mixing it with citric acid and ethylene glycol in a molar ratio of 1:2. The carrier was placed in the impregnation solution and impregnated at a constant temperature of 60℃ in a water bath for 6 hours. The nickel precursor was uniformly anchored through the interface confinement of the carrier and the coordination of the additives. After impregnation, the carrier was dried at a constant temperature of 110℃ for 8 hours to obtain the carrier loaded with the nickel-based precursor.

[0051] Step 3: Weigh sodium hypophosphite according to a Ni / P molar ratio of 1:1, mix it uniformly with the carrier supporting the nickel precursor, place it in a tubular reactor, and purify it with high-purity nitrogen gas throughout the process. The gas flow rate is 50 mL / min, and the phosphating reaction is carried out at a constant temperature of 300℃ for 2 hours to induce the preferential growth of Ni2P (201) and (211) highly active crystal faces in situ. After the reaction, cool it under a nitrogen atmosphere and passivate it with a low-concentration oxygen-nitrogen mixture. After granulation, crushing, and sieving, select 40-60 mesh particles to obtain the hydrodechlorination catalyst.

[0052] Results: The hydrodechlorination catalyst prepared in this comparative example can remove organochlorine and generate HCl, with an organochlorine removal efficiency of 75% and an HCl selectivity of 78%.

[0053] Comparative Example 3: A method for preparing a hydrodechlorination catalyst includes the following steps: Step 1: Preparation of LDH-hierarchical porous ZSM-5 composite support: Pure LDH material was placed in a muffle furnace and heated to 500℃ at a rate of 10℃ / min, and calcined at this temperature for 4 hours to obtain LDO layered bimetallic oxide. LDO powder was dispersed in a 10% (w / w) aqueous solution of NH4H2PO4 and stirred at room temperature for 5 hours to utilize the LDO memory effect to complete structural reconstruction and phosphate anion intercalation. Subsequently, a mixed metal salt solution of nickel formate and ferric nitrate nonahydrate was slowly added and thoroughly mixed to construct interface sites suitable for Ni2P growth. The mixed slurry was dried at 120℃ for 12 hours and calcined at 450℃ for 3 hours to obtain the LDH-based support.

[0054] Using sodium alginate as a green polysaccharide template, hierarchical ZSM-5 molecular sieves were prepared by hydrothermal crystallization at a crystallization temperature of 180℃ and a crystallization time of 12h. Hydrogen bonds were formed between the hydroxyl groups on the surface of sodium alginate and the (010) crystal facets of ZSM-5 to regulate the crystal morphology and chelate the active precursor. After drying, the crystallized product was calcined at 450℃ for 2h to completely remove the polysaccharide template and construct a hierarchical porous structure in situ, thus obtaining functionalized hierarchical ZSM-5 molecular sieves.

[0055] The obtained polysaccharide-modified porous ZSM-5 was compounded with LDH-based support at a mass ratio of 1:1, and deionized water was added and stirred thoroughly to disperse the mixture. After conventional drying and calcination at 450℃, the LDH-multi-level porous ZSM-5 composite support was obtained.

[0056] Step 2: Preparation of composite supports for nickel-based precursors: Nickel nitrate was weighed at 10 wt% of the theoretical nickel loading to prepare an impregnation solution. The composite carrier was placed in the impregnation solution and impregnated at a constant temperature of 60°C in a water bath for 6 hours. The nickel precursor was uniformly anchored through the interface confinement of the carrier and the coordination of the additives. After impregnation, the composite carrier loaded with nickel-based precursor was dried at a constant temperature of 110°C for 8 hours to obtain the composite carrier.

[0057] Step 3: Weigh sodium hypophosphite according to a Ni / P molar ratio of 1:1, mix it uniformly with the composite support carrying the nickel precursor, place it in a tubular reactor, and purify it with high-purity nitrogen gas throughout the process. The gas flow rate is 50 mL / min, and the phosphating reaction is carried out at a constant temperature of 300℃ for 2 hours to induce the preferential growth of Ni2P (201) and (211) highly active crystal faces in situ. After the reaction, cool it under a nitrogen atmosphere and passivate it with a low-concentration oxygen-nitrogen mixture. After granulation, crushing, and sieving, select 40-60 mesh particles to obtain the hydrodechlorination catalyst.

[0058] Results: The hydrodechlorination catalyst prepared in this comparative example can remove organochlorine and generate HCl. The removal efficiency of organochlorine is only 73%, while the selectivity of HCl can reach 71%.

[0059] Experiments were conducted on the catalysts prepared in Examples 1 to 7 and Comparative Examples 1 to 3, and their dechlorination efficiency and HCl selectivity were as follows: Figure 1 As shown in the comparison, adjusting the ratio of the carrier compound and the ratio of citric acid to ethylene glycol both affect the dechlorination performance. The comparative examples without LDH, using traditional organic amine templates, or without adding crystal facet control agents have significantly lower organic chlorine removal efficiency and HCl selectivity than Example 1. This proves that the composite carrier of the present invention, together with the polysaccharide template and compounding agents, can significantly improve the low-temperature hydrogenation dechlorination activity and resistance to chlorine poisoning.

[0060] Following the guidance of Examples 1 to 7 above, those skilled in the art can also use cobalt nitrate nonahydrate or copper nitrate nonahydrate instead of ferric nitrate nonahydrate.

[0061] Any parts not mentioned in this invention can be achieved by referring to existing technologies.

[0062] Those skilled in the art should recognize that the above embodiments are merely illustrative of this application and are not intended to limit this application. Any appropriate changes and variations made to the above embodiments within the essential spirit and scope of this application should fall within the scope of protection of the claims of this application.

Claims

1. A method for preparing a hydrodechlorination catalyst based on a sugar-template-modified ZSM-5 composite support supporting Ni2P crystal planes, characterized in that, The preparation method includes the following steps: a. Preparation of LDH-hierarchical porous ZSM-5 composite carrier: Polysaccharide-modified porous ZSM-5 is used as the main body and compounded with LDH-based carrier. After dispersion, drying and calcination, LDH-hierarchical porous ZSM-5 composite carrier is obtained; wherein, the mass ratio of polysaccharide-modified porous ZSM-5 to LDH-based carrier is 1~4:1~4. b. Preparation of composite support for nickel-based precursor: Nickel nitrate, citric acid and ethylene glycol are mixed to prepare an impregnation solution; the LDH-hierarchical porous ZSM-5 composite support is placed in the impregnation solution, and a water bath constant temperature equal volume impregnation method is used. Through the interfacial confinement of the LDH-hierarchical porous ZSM-5 composite support and the coordination effect of ethylene glycol, the nickel active component is uniformly anchored and its growth sites are controlled. After impregnation, the composite support for nickel-based precursor is obtained by constant temperature drying. c. The composite carrier supporting the nickel-based precursor and sodium hypophosphite are placed in a tubular reactor, and Ni2P201 and Ni2P211 crystal planes are preferentially grown in situ under a nitrogen atmosphere. After the reaction is completed, the mixture is cooled and passivated under an inert atmosphere, and then granulated, crushed, and sieved to obtain 40-60 mesh particles.

2. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 1, characterized in that: In step a, the preparation steps of polysaccharide-modified porous ZSM-5 are as follows: using green biological polysaccharide as a template, it is dissolved and thoroughly mixed with porous ZSM-5 precursor. Hydrogen bonds are formed between the hydroxyl groups on the surface of the biological polysaccharide and the 010 crystal facet of the ZSM-5 precursor to anchor and control the crystal facet morphology. The resulting mixed gel is placed in a hydrothermal reactor for hydrothermal crystallization reaction. After crystallization, it is cooled to room temperature and dried. The precursor powder is then placed in a muffle furnace for calcination. After grinding and filtration, the product is obtained.

3. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 2, characterized in that: The green biopolysaccharide is sodium alginate or chitosan; a porous ZSM-5 precursor is prepared by hydrothermal crystallization at a temperature of 160–200°C for 12 hours; the precursor is then calcined in a muffle furnace at a temperature of 400–500°C for 2–3 hours, during which the green biopolysaccharide is thermally desorbed.

4. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 1, characterized in that: In step a, the preparation steps of the LDH-based support are as follows: calcining layered double hydroxide LDH to obtain layered bimetallic oxide LDO, dispersing the obtained layered bimetallic oxide LDO powder in NH4H2PO4 aqueous solution, and using the LDO memory effect to complete the structure reconstruction and anion intercalation; then adding nickel formate and transition metal salt solution and mixing evenly to construct interface sites suitable for the subsequent growth of Ni2P active components, and then drying and calcining to obtain the LDH-based support.

5. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 4, characterized in that: In step a, the calcination temperature is 500℃ and the calcination time is 4h, while the roasting temperature is 400~500℃ and the roasting time is 2~3h.

6. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 4, characterized in that: In step a, the transition metal salt is an iron salt, cobalt salt, or copper salt, the mass fraction of the NH4H2PO4 aqueous solution is 5%–15%, and the anion intercalation stirring time is 5–6 h.

7. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 1, characterized in that: In step b, the impregnation temperature is 60℃ and the impregnation time is 6h; the molar ratio of citric acid to ethylene glycol is 1:1 to 3; the loading of metallic nickel in the hydrodechlorination catalyst is 5 to 15 wt%; the constant temperature drying temperature is 100 to 120℃ and the drying time is 6 to 12h.

8. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 1, characterized in that: In step c, the composite carrier loaded with the nickel-based precursor and sodium hypophosphite are placed in a tubular reactor and the Ni:P molar ratio is controlled to be 1-2:1-2. The reaction temperature in the tubular reactor is 250-350℃ and the constant temperature reaction time is 1-3h.

9. The method for preparing a hydrodechlorination catalyst based on a sugar-template modified ZSM-5 composite support supporting Ni2P crystal planes according to claim 1, characterized in that: In step c, the reaction is carried out under a nitrogen inert atmosphere, and the nitrogen gas flow rate is controlled at 50 mL / min.

10. A hydrodechlorination catalyst based on Ni2P supported on a sugar-templated modified ZSM-5 composite support, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9, and the dechlorination conditions of the hydrodechlorination catalyst are: 20 ml·min ‐1 A mixture of chlorobenzene and nitrogen gas at 20 ml / min ‐1 The H2 in the mixture is 100 ppm chlorobenzene, the dechlorination temperature is 300℃, and the dechlorination time is 30 min.